Voltammetric Analysis of Herbicide Picloram on the Silver Solid Amalgam Electrode - Janíková, Lenka; Šelešovská, Renáta; Chýlková, Jaromíra; Nesnídalová, Věra (My University, 2016)
A silver solid amalgam electrode was employed for the first time for the determination of the pyridine herbicide picloram. The voltammetric behavior of this herbicide was studied using cyclic, direct current, and differential pulse voltammetry on the mercury meniscus modified silver solid amalgam electrode. All results were compared with those achieved on the classic hanging mercury drop electrode. One reduction signal, which was suitable for analytical purposes, was recorded on the amalgam electrode after addition of picloram. The current response of the herbicide increased linearly in the concentration range from 1x10(-7) to 8x10(-5)moles per liter, and a limit of detection of 8.78x10(-8)moles per liter was obtained using differential pulse voltammetry under the optimized conditions. The selectivity and applicability of the voltammetric technique was verified by an interference study and analysis of fortified environmental samples with excellent recoveries: 100.0%(tap water), 100.5% (dam water), and 95.0% (river water).
Voltametrické stanovení herbicidu picloramu s využitím stříbrné pevné amalgámové elektrody
Keywords: Herbicide; picloram; reduction; silver solid amalgam electrode; voltammetry; Herbicid; picloram; redukce; stříbrná pevná amalgámová elektroda; voltametrie